Quantification of Treg cells in peripheral blood and lymph nodes of dogs with multicentric lymphoma - Anai, L. A. [UNESP]; Munhoz, T. D.; Semolin, L. M.S. [UNESP]; Filho, N.P. Reis [UNESP]; Terra, E. M. [UNESP]; Jark, P. C. [UNESP]; Fonseca, D. M. [UNESP]; Nogueira, A. F.S.; Tinucci-Costa, M. [UNESP]; Santana, A. E. [UNESP] (FapUNIFESP (SciELO), 2017)
Lymphoma is a malignant tumor characterized by cell proliferation of lymphoid origin and corresponds to 90% of all hematopoietic neoplasms of dogs. Regulatory T cells (Tregs) have been the target of many investigations in oncology due to their potential of down-regulating immune responses, as well as ensuring the maintenance of active mechanisms of tumor suppression. The aims of the present study were to compare the percentage of Tregs in peripheral blood between dogs with multicentric lymphoma and healthy animals, together with the percentage of Tregs in peripheral blood and lymph nodes of dogs with multicentric lymphoma. Twenty-six animals were enrolled in the study: 10 healthy dogs comprised the control group (CG) and 16 dogs with multicentric lymphoma comprised the Lymphoma Group (LG). We observed that dogs in the LG showed a significantly higher Tregs expression in peripheral blood compared to the CG. No significant difference was observed between Tregs expression in lymph nodes and peripheral blood of the LG, however. With these results, it is possible to conclude that multicentric lymphoma is a neoplasm with high Tregs expression, which poses this as a condition of interest when investigating treatments that can suppress Regulatory T cells.
Keywords: Canine; Foxp3; Lymphoma; Regulatory T cells